HUBUNGAN LAMA PEMBERIAN DIET ATEROGENIK TERHADAP KADAR KOLESTEROL TOTAL Rattus novergicus JANTAN STRAIN WISTAR - Pratiwi, Fanny; Asni, Enikarmila; ", Fridayenti; ", Ismawati (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTCardiovascular disease is the number one cause of death globally in the world. One of the cardiovascular risk factor is hypercholesterolemic, signed by high total cholesterol levels in the blood. The purpose of this research is to know the correlation of given atherogenic diet duration toward total cholesterol level in male Wistar rat. This research is an experimental research with the post test-only control group design approach using 2-3 months old male rats (Rattus novergicus) with 160-240 g average weight range. The rats were divided into 4 groups such as control group given with standard diet, the 5 weeks atherogenic diet group, the 8 weeks atherogenic group, and the 12 weeks atherogenic group, each group consists of 6 rats. The atherogenic diet (2% cholesterol of egg yolk, 5% goat’s fat, and 0,2% cholic acid) is given amount to 20 g/each/day. Then cholesterol total serum was measured with CHOD-PAP method in the fifth week ,the eighth week and the twelfth week. The result of this research shows a significant difference (p=0,000). As for the post hoc test (p=0,000), there is a statistically significant difference within the experimental groups. In the Spearman test (0,967), there is a significant positive correlation between the given duration of the atherogenic diet toward the total cholesterol level. In this research we can conclude that the longer duration of the atherogenic diet is, the higher the cholesterol total in male Wistar rats (Rattus novergicus) will be.Keywords : Atherogenic diet, total cholesterol, rats (Rattus novergicus)